Inspiration from vitreoretinal fellow training program in Columbia University - HAN Liang, ZHUO Yan-ling (Jichu yixue yu linchuang, 2022)
The resident standardized training program of ophthalmology in China has been carried out widely. However, the vitreoretinal fellow training program has not been established. This article describes the vitreoretinal fellow training program both in Department of Ophthalmology of Columbia University and Ophthalmology Center of Peking University Third Hospital, and the differences of the two programs are also analyzed. It aims to build a Chinese vitreoretinal fellow training program, so more qualified vitreoretinal doctors will be trained through this program.